Optimizing Family Medicine Outcomes through the Integration of Nursing, Pharmacy, and Public Health Strategies - Amal Yahya Mohammed Asiri; Abeer Dhaifallah Fayz Alshehri; Norah Ahmed Marei Alshmrani; Bashayr Rafdan Safar Alshahrani; Afnan Ali Aiedh Saeed; Maha Saad Mohammad Alahmari; Lamyaa Saad Saed Alshahrani; Fatmah Mohammed Blqassim Alamri; Fatmah Mohammed Ahmad Althabet; Norah Saad Alqahtani (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The provision of primary health care ensures that health needs within the family medicine spectrum are met. The emphasis on family medicine practice is on the provision of multi-faceted and multidisciplinary approaches to address health issues. The application of nursing, pharmacy and public health strategies in family medicine practice is effective in improving the quality of care and satisfaction of patients and health outcomes of populations especially given the chronic conditions, high healthcare costs, and inequalities in health. Aim of work: To investigate the influence of integration betweennursing, pharmacy, and public health strategies inoptimizing family medicine outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Optimizing, Family Medicine, Outcomes, Integration, Nursing, Pharmacy, and Public Health Strategies. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In the field of family medicine, there is a significant shift that occurs with the incorporation of nursing, pharmacy, and public health. It is a logical step forwards as if each of them is a unique building block in achieving family medicine objectives in maximizing health, ensuring equity, and dealing with intricate issues embedded in present-day health. Teamwork is vital as it improves quality care and also increases the availability of preventive services, and fortifies the health system for eventualities. In as much as there are constraints to this integration, there are already optimistic possibilities where family medicine may overcome these limitations through policy, educational, and technological reform.